To evaluate the prevalence of digital burnout among medical science students and correlate the levels of digital burnout with other demographic variables - Nisha Shainy Daud (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2025)
Background: Frequent use and exposure to digital devices in both academic and personal settings predisposes university students to digital burnout. Objective: To evaluate the incidence of digital burnout among medical science students and to associate the levels of digital burnout with diverse demographic characteristics. Methods: A descriptive cross-sectional study was done using convenient sampling among 300 students (86.3% male, 13.7% female) across various programmes and academic levels. The instruments employed for data collection were Tool 1 - Demographic Data and Tool 2 - Digital Burnout Scale (DBS). Findings: The findings indicated that 75% of the students experienced moderate to mild burnout. In general, and across all subcategories, average ratings reflect moderate levels of burnout. A notable disparity in digital burnout was identified among age groups (F=4.62, p=0.011), with individuals aged 24 and above exhibiting the highest levels of burnout relative to their younger peers. A statistically significant difference was observed in digital burnout scores among groups categorised by online duration, specifically beyond 6 hours (F = 4.52; p = 0.007). The study reveals that students experience moderate burnout, correlated with age and duration of gadget usage. Conclusion: Specific strategies are necessary to mitigate digital burnout, particularly among seniors and individuals who engage extensively with online platforms. Institutions must thoroughly investigate the implementation of programs to foster better digital habits and offer resources that enhance students' well-being in progressive digital academic settings